The occupation of the Russian city of Voronezh by German forces 1942-1943: A study in Russian Sources and Documents - AlNoora, Maher (Al-Adab Journal, 2023)
The Russian city of Voronezh, which is of great strategic importance due to its location on the Don River, was subjected to a violent attack by German forces as an opening step for the German summer offensive, which began on 28 June  1942, and this attack coincided with the beginning of the Nazi campaign on the Eastern Front during World War II, The German attack on the city of Voronezh had two main goals, one of which was to shade the final goals of the campaign, and the other and more important goal was to provide an easily defendable front line along the Don River that could be protected by using relatively light forces.       As for the Soviet side, there was a widespread view among all observers, especially the Soviet high command, that the Germans prepared to attack Moscow that summer by attacking strongly towards the city of Voronezh, and that Soviet forces sent to the region to support the defenses would not be able to move with the same The speed of the Germans by then had turned south and left the Soviet army behind.       The research is divided into two main axes. In this first axis, we touched on the German occupation of Voronezh and the Soviet position on it, which included the conduct of military operations on the outskirts of Voronezh and the Germans’ control of the right part of the city on 28 June  1942, and their control over it continued until the 25  of January 1943 approximately 212 days. While in the second axis we dealt with the Soviet measures to restore the city and address what was left by the occupationAfter the occupation of the city, the Soviet leadership issued strict measures that had a great resonance in regaining control of the city, and during the occupation period several serious attempts were made to regain control over it, the last of which succeeded and proved the worth of the Soviet forces in defending it and the extent of the adherence of its people and their steadfastness in the battles that took place. On their land until full control was regained in late January 1943 , and We also talked about the crimes and damage caused to the city as a result of the German occupation and the means taken by the Soviet government to rebuild the city.         In this research, we relied on a group of sources, documents and some letters of the Soviet leadership, including written official orders, including letters published on YouTube. The Soviet official newspapers, which were issued during the days of the German occupation of Voronezh, had a great role in providing us with detailed information that helped the researcher give a clear picture. On the number of forces of the warring parties and the general situation in the city during the days of the occupation, and on the strict measures and orders taken by the Soviet leadership against those who failed to defend the city until the city was restored and returned to the arms of the Soviet authority. It took place inside the city and on its outskirts, and about the size of the losses on both sides.